Pharmacological effects, molecular mechanisms, and pharmacokinetics of benzoylaconine: a systematic review - Zhuang, Huamei; Yao, Hong (Frontiers in Pharmacology, 2025)
Benzoylaconine (BAC), a key active metabolite in traditional Chinese medicine, is derived from the subsoil roots of Fuzi (Aconitum carmichaelii Debx [Ranunculaceae, Aconitum carmichaelii Debx roots]). BAC has garnered considerable research attention because of its therapeutic effects against cardiovascular disease, inflammation, and arthritis, and this has led to continual updates in the literature. This systematic review summarizes evidence on the pharmacological effects, molecular mechanisms, and pharmacokinetics of BAC. PubMed and Web of Science were searched for relevant articles published between January 2000 and November 2024. Genes, proteins, and pathways related to the activity and therapeutic effects of BAC were identified. BAC usually targets proteins such as ACE2, IL-6, MAPK, PI3K, Akt, STAT3, TNF-α, and VEGF. The identified genes and proteins were subjected to protein–protein interaction analysis, molecular docking between BAC and protein hubs, and bioinformatic analyses (gene ontology, Kyoto Encyclopedia of Genes and Genomes, and disease ontology analyses). Protein–protein interaction analysis and molecular docking indicated IL-6, Akt1, and STAT3 as key targets of BAC. These findings offer theoretical insights into the potential therapeutic mechanisms of BAC and may inform its future development as a pharmacological agent.